2001
DOI: 10.1021/ja0020963
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and FTIR Spectroscopic Evidence of Changes in Fe Coordination Upon Reduction of the Active Site of the Fe-Only Hydrogenase fromDesulfovibriodesulfuricans

Abstract: Fe-only hydrogenases, as well as their NiFe counterparts, display unusual intrinsic high-frequency IR bands that have been assigned to CO and CN(-) ligation to iron in their active sites. FTIR experiments performed on the Fe-only hydrogenase from Desulfovibrio desulfuricans indicate that upon reduction of the active oxidized form, there is a major shift of one of these bands that is provoked, most likely, by the change of a CO ligand from a bridging position to a terminal one. Indeed, the crystal structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

55
920
3
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 765 publications
(989 citation statements)
references
References 47 publications
55
920
3
2
Order By: Relevance
“…X-ray crystallography and FTIR spectroscopy have shown that the three enzymes are characterized by complex active sites that have in common a Fe(CO) x unit, and, in the case of [NiFe]-and [FeFe]-hydrogenases, two CN À ligands ( Fig. 1) [5][6][7][8][9]. However, the [NiFe]-and [FeFe]-hydrogenases do not use the same molecular strategy to link the two metal ions of the dinuclear site: whereas two protein-bound cysteines provide the two sulfur bridges in [NiFe]-hydrogenases, this bridge in [FeFe]-hydrogenases is provided by a non-protein dithiolate ligand, whose composition has not been determined experimentally but was proposed, on the basis of X-ray crystallographic data, to be À SCH 2 XCH 2 S À , with X being either nitrogen, oxygen or carbon [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystallography and FTIR spectroscopy have shown that the three enzymes are characterized by complex active sites that have in common a Fe(CO) x unit, and, in the case of [NiFe]-and [FeFe]-hydrogenases, two CN À ligands ( Fig. 1) [5][6][7][8][9]. However, the [NiFe]-and [FeFe]-hydrogenases do not use the same molecular strategy to link the two metal ions of the dinuclear site: whereas two protein-bound cysteines provide the two sulfur bridges in [NiFe]-hydrogenases, this bridge in [FeFe]-hydrogenases is provided by a non-protein dithiolate ligand, whose composition has not been determined experimentally but was proposed, on the basis of X-ray crystallographic data, to be À SCH 2 XCH 2 S À , with X being either nitrogen, oxygen or carbon [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the [NiFe]-and [FeFe]-hydrogenases do not use the same molecular strategy to link the two metal ions of the dinuclear site: whereas two protein-bound cysteines provide the two sulfur bridges in [NiFe]-hydrogenases, this bridge in [FeFe]-hydrogenases is provided by a non-protein dithiolate ligand, whose composition has not been determined experimentally but was proposed, on the basis of X-ray crystallographic data, to be À SCH 2 XCH 2 S À , with X being either nitrogen, oxygen or carbon [10]. Because of the potential role of an amine group in proton trafficking, we consider the first hypothesis as the most likely [9].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the [Fe 2 (SR) 2 L 6 ] framework approaches that proposed for the H ox state of the active site. [2,9] Of specific interest, the oxidation has caused the {Fe(CO)(dppv)} center to rotate about the Fe-Fe axis. The apical site on the {Fe(dppv)} center is vacant, and the [BF 4 ] − anion is approximately 5 Å away from this "distal" Fe center.…”
mentioning
confidence: 99%
“…1-5 These efforts are motivated by the following considerations: (i) the possibility that the azadithiolate is the dithiolate cofactor in the Fe-only hydrogenases, 6 (ii) the possibility that such a ligand could play a functional role in the heterolytic activation of H 2 ,7,8 and (iii) the amine is a versatile point of attachment for diverse substituents. 4,5 The functionalization of organometallic sulfides is an active area.…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractReaction of Fe 2 (SH) 2 (CO) 6 and HCHO, which gives Fe 2 [(SCH 2 ) 2 NH](CO) 6 in the presence of NH 3
…”
mentioning
confidence: 99%